ANALISIS PENERAPAN E-REGISTRATION, E-BILLING, E-FILLING DAN E-SPT TERHADAP PEMAHAMAN PERPAJAKAN DALAM KEPATUHAN WAJIB PAJAK BADAN (STUDI KASUS UMKM PEKANBARU KOTA) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This aims of the study to analyze the implementation of e-registration, e-filling, ebilling, and e-spt on the understanding of taxation in corporate taxpayer compliance at UMKM Pekanbaru City. The populations in this study were UMKM corporate taxpayers in Pekanbaru City which were active and registered at the Department of Industry and Trade of Riau Province, so that the sample obtained 48 corporate taxpayers with total sampling technique. Data were analyzed using path analysis by SmartPLS version 3.2.8 software. The results of the study concluded that e-billing, e-filling, e-spt, and tax understanding had a significant positive effect on taxpayer compliance. Meanwhile, eregistration has no effect on Taxpayer Compliance. In addition, from the path analysis, it is known that e-billing, e-filling and e-spt, has positive significance effect on Taxpayer Compliance through Tax Understanding. Meanwhile, the e-registration has no significance positive effect on Taxpayer Compliance through Tax Understanding. In additon, based on the results of the R Square analysis, it is known that the effect of eregistration, e-billing, e-filling, and e-spt on the understanding of taxation is 94.0%, including in the strong category, the Q square of understanding taxation is 0.845, which means the the effect of e-registration. , e-billing, e-filling and e-spt predict that understanding of taxation was the strong category. The R square analysis of taxpayer compliance is 0.928, which means that the effect of e-registration, e-billing, e-filling, espt and understanding of taxation on taxpayer compliance is 92.8%, categorized as strong category, Q square understanding of taxation was 0.800 means that the ability of e-registration, e-billing, e-filling, e-spt and understanding of taxation predicts that taxpayer compliance categorized as strong category.Key Words: e-registration, e-billing, e-filling, e-spt, understanding of taxation, taxpayer compliance, UMKM